Diversity, Virulence, and Clinical Significance of Extended-Spectrum β-Lactamase- and pAmpC-Producing Escherichia coli From Companion Animals - Bortolami, Alessio; Zendri, Flavia; Maciuca, Elena Iuliana; Wattret, Andy; Ellis, Christine; Schmidt, Vanessa; Pinchbeck, Gina; Timofte, Dorina (Frontiers in Microbiology, 2019)
Escherichia coli are opportunistic pathogens with the potential to cause a variety of infections in both humans and animals and in many cases have developed antimicrobial resistance. In this study, we characterized extended-spectrum cephalosporin resistant (ESCR) E. coli isolates from diseased companion animals (dogs, cats, and horses) and related the results to clinical findings. ESCR E. coli clinical isolates obtained over a 6-year period were screened for extended-spectrum β-lactamase (ESBL) and/or plasmid mediated AmpC (pAmpC) and virulence markers likely to be associated with extraintestinal pathogenic E. coli (ExPEC). ESBL and/or pAmpC genetic determinants were identified in 79.9% of the ESCR E. coli isolates with blaCTX-M genes being the most common ESBL genotype of which blaCTX-M-15, blaCTX-M-14, and blaCTX-M-55 were the most prevalent. In addition, blaCMY -2 was the most common genotype identified amongst pAmpC producing isolates. Phylogenetic group typing showed that B2 was the most prevalent phylogroup among the ESCR E. coli isolates, followed by the closely related phylogroups D and F which are also associated with extra-intestinal infections. ESCR was also identified in phylogroups commonly regarded as commensals (B1, A, and C). Virulence factor (VF) scores >2 were mostly present amongst isolates in phylogroup B2. Higher virulence scores were found in isolates lacking ESBL/pAmpC resistance genes compared with those carrying both genes (p < 0.05). Five of phylogroup B2 isolates, were typed to the pandemic virulent O25b-ST131 clone and three ST131 isolates carrying blaCTX-M-15 belonged to the subclade C2/H30Rx whilst one isolate carrying blaCTX-M-27 typed to the recently described sub-clade C1-M27. MLST typing also identified other sequence types commonly associated with infections in humans (ST410, ST10, and ST648). Most ESCR E. coli isolates obtained in pure growth were cultured from normally sterile body sites (mostly from urinary tract infections, UTIs) whilst only a small proportion were obtained from body sites populated with commensal flora (p < 0.0001). Our study has shown that ExPEC ESBL/pAmpC producing E. coli isolates are common amongst companion animal isolates and are associated with colonization and infection. In addition, their isolation from a normally sterile site is likely to be clinically significant and warrants antimicrobial treatment.